Knowledge Co-Production: Nurturing Grassroots Innovations within Environments of Scarcity. The Case of Community Currency in Kisumu, Kenya - Oloko, Michael; Kiaka, Richard (European Journal Of Social Sciences Studies, 2026)
Although grassroots innovations often emerge in contexts of scarcity, they rarely fulfil the purposes that originally prompted their inception. Limited local capacity to nurture and protect such initiatives can create opportunities for ‘elite capture’ by more privileged and resourceful actors. This paper brings together two seemingly antagonistic concepts— ‘elite capture’ and ‘knowledge co-production’—to inform the introduction and implementation of a community currency as a grassroots innovation in Kisumu. It draws on experiences and lessons learnt from similar initiatives in Mombasa and Nairobi, and applies the principles of knowledge co-production to prevent ‘elite capture’ in Kisumu. The inclusive nature of the knowledge co-production approach—accommodating relevant stakeholders and their diverse interests—its goal-oriented focus, and its emphasis on effective collaborative engagement, combined with the flexibility to allow iterative processes, are employed to safeguard the interests of the most deserving local participants. The paper advances understanding of knowledge co-production and demonstrates its application in facilitating constructive engagement and stakeholder participation to prevent ‘elite capture’. Together, these elements help to ensure local ownership and management of innovations by their intended beneficiaries, thereby strengthening local support mechanisms and empowering the community.
Keywords: Grassroots; Innovation; Community Currency; Elite Capture; Knowledge Co-Production